Forest Structure and Tree Species Diversity of the Abasumba Globally Significant Biodiversity Area, Ghana - Felix Tetteh Kabutey; Daniel Wodah (Universitas Gadjah Mada, 2023)
We studied the forest structure and tree species diversity with diameter-at-breast-height (dbh) ≥ 10 cm in the Abasumba Globally Significant Biodiversity Area Ghana. Sixteen 25 m * 25 m plots were demarcated and trees with dbh ≥ 10 cm were inventoried following International Plant Nomenclature Index. The characteristic three–storey structure of tropical forests was shown, 68.7% of trees were in the lower 4.5–18 m and middle 18–30 m storeys. A majority 91.4% of 342 trees was in the dbh of 10–30 cm and a least 8.6% of 32 trees in 31–60 cm had dbh ˃ 60 cm. Total of 46 species, 38 genera and 17 families, with mean Alpha, Shannon and Simpson’s Diversity indices of 13.9, 1.44 and 0.07 and importance value index of 300.0 for 374 trees ha-1 was recorded. Plant families Sterculiaceae, Meliaceae, Leguminosae, Ulmaceae and Bombacaceae was the majority encountered while Triplochiton scleroxylon, Cola millenii, Trichilia monadelpha, Hymenostegia afzelii, Celtis mildbraedii, Ceiba pentandra and Ficus sur was the most occurring species in 54.0% of the plots accounting for 52.0% of the IVI for all trees. Blighia sapida, Bridelia grandis, Dialium guineense, Draceana arborea, Ficus sur, Holarrhena floribunda, Holoptelea grandis, Margaritaria discoidea, Rauvolfia vomitoria, Trilepisium madagascariense, Vitex ferruginea, Ximenia americana and Xylia evansii had one individual in the 10,000 m2 area indicated that they are rare and should be given conservation priority in the forest reserve.